Desenvolvimento e produtividade do boldo brasileiro submetido a lâminas de irrigação - Rosal, Gilbenes Bezerra (2021)
The Brazilian boldo (Plectranthus barbatus Andrews), in addition to being widely cultivated as an ornamental plant, has important medicinal properties, which generate commercial interest for it. Irrigation in northeastern Brazil is a practice used for plant survival and increased crop productivity, however, the Brazilian Boldo is still a poorly researched crop in the country, mainly regarding its water needs. Thus, the objective was to evaluate the effects of the application of irrigation depths on the development, productivity of Brazilian boldo and substrate fertility. The experiment was conducted at the Fazenda Experimental Piroás (FEP) of the Universidade Internacional da Lusofonia Afro-Brasileira (UNILAB), located in the Barra Nova district in Redenção-CE, in the Maciço de Baturité region. The experimental design was randomized blocks with five treatments, four blocks and three useful plants. The treatments consisted of applying irrigation depths calculated as a function of crop evapotranspiration - ETc (equivalent to 33; 66; 100; 133 and 166% of ETc). Plant height, stem diameter, number of leaves, fresh and dry mass of leaves, stem, root and shoot, length of the root, root / shoot ratio, fresh and dry leaf yield, length and width of leaves, water use efficiency and substrate fertility were analyzed. From the results obtained, it was observed that the greatest crop growth was achieved with the irrigation depth corresponding to 166% of the ETc (1,379 mm), while the irrigation depth corresponding to 132% of the ETc (1,111 mm) provided the highest productivity in fresh mass of Brazilian boldo. The depth equivalent to 33% of the ETc (331 mm) provided the highest water use efficiency, while the substrate fertility was not influenced by the treatments, except for the pH, which was less alkaline for the lowest irrigation depth. Considering the results obtained, the irrigation depth corresponding to 132% of the ETc (1,111 mm) is recommended for the cultivation of Brazilian boldo.